Reshaping relational scripts? Marriage and civil partnership proposals among same-gender couples. Issue 4 (2nd October 2019) - Jowett, Adam; Peel, Elizabeth
ABSTRACT: The traditional marriage initiation script entails male partners 'proposing' to female partners. However, little is known about how same-gender couples initiate a marriage or civil partnership. Drawing on qualitative survey data from 82 people in a UK civil partnership or same-gender marriage we identify two marriage initiation themes which foreground the reshaping of script norms for marriage proposals. The first theme, 'queer proposals' entails an adaptation of the conventional script. The second theme 'jointly negotiated initiations', foregrounds a fundamental departure from heteronormative scripts for initiating the legal formalisation of a relationship. It is argued that the non-normative status of such partnerships not only allow for alternative scripts to socially emerge, but offer a reconceptualization of a cultural script grounded in heteronormative relationship practices. The study therefore makes an important contribution to our understanding of same-gender relationship practices and has significant implications for sexual script theory.